2012
DOI: 10.7448/ias.15.6.18096
|View full text |Cite
|
Sign up to set email alerts
|

Adherence and retention on antiretroviral therapy in a public‐private partnership program in Nigeria

Abstract: Initiation of HIV-positive patients on antiretroviral therapy (ART) in Nigeria was restricted to secondary and tertiary level hospitals due to weak health systems in primary health centres (PHCs). Shell Petroleum Development Company (SDPC) Nigeria and FHI 360 using a systems strengthening approach, piloted ART enrolment in a PHC in south-eastern Nigeria. This study sought to evaluate patients’ adherence and mortality on ART, and associated risk factors. We reviewed clinic records of adult patients initiating A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Antiretroviral Therapy (ARV) require HIV/AIDS sufferers to be more consistent in taking medication for life, so it takes a high commitment from PLWHA to survive longer. (7)(8)(9)(10)(11)22) The results of this study indicate the reasons for LTFU patients related antiretroviral therapy are influenced by multy factors, this is also supported by their predisposing factors . (23) This was shown by patients whose LTFU turned out to have a CD4 cell count> 350 cells / mm 3 more than retention patients, so they felt healthy and finally did not want any more ARV therapy.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Antiretroviral Therapy (ARV) require HIV/AIDS sufferers to be more consistent in taking medication for life, so it takes a high commitment from PLWHA to survive longer. (7)(8)(9)(10)(11)22) The results of this study indicate the reasons for LTFU patients related antiretroviral therapy are influenced by multy factors, this is also supported by their predisposing factors . (23) This was shown by patients whose LTFU turned out to have a CD4 cell count> 350 cells / mm 3 more than retention patients, so they felt healthy and finally did not want any more ARV therapy.…”
Section: Discussionmentioning
confidence: 53%
“…(3,(6)(7)(8) Antiretroviral treatment (ARV) requires HIV/AIDS patients to be more consistent in taking medication for a lifetime, so it takes a high commitment from PLWHA to survive longer. (9)(10)(11) This has led to an increase in the discovery of cases of Loss to follow-up (LTFU), based on the HIV and AIDS Information System of the Indonesian Ministry of Health until September 2017 it was found data of LTFU 43,707 ( 22%), for Central Java from 2005 to August 2018 data Loss to Follow up: 3.227 people (23%). (3) Research in Zambia and Switzerland on observations of three and a half years of therapy showed an LTFU percentage of 29.3% in patients starting ART with a CD4 count <100 cells/ml and 15.4% for patients starting with ≥ 350 cells/ mL .…”
Section: Introductionmentioning
confidence: 99%
“…Study health outcomes are ART adherence [ 23 , 30 , 31 ], viral load, retention in care [ 32 , 33 ], and condom use ( Table 1 ). Routine data collection for clinical care related to ART adherence and health outcomes and tracking already occurs in the public sector NACP/GHS health facilities.…”
Section: Methodsmentioning
confidence: 99%